Probing the Fusion of Arabic and Gorontalo Dialect in the Daily Linguistic Landscape of Students at Al-Falah Islamic Boarding School - Jundi, Muhammad; Hasibuan, Renni; Kadir, Suleman D. (Kitabina: Jurnal Bahasa dan Sastra, 2023)
This study aims to delineate the attributes of the day-to-day usage of the Arabic language by students at Pondok Pesantren Al-Falah Limboto Barat, considering the intrusion of the learners' native language, predominantly the Gorontalo regional dialect. The employed research methodology adopts a qualitative descriptive stance, encompassing data accrual through interviews and observations. Subsequently, the data undergoes scrutiny via deductive and descriptive approaches. The revelations of this investigation are expounded upon in five intricately linked sub-dialogues. Initially, the adeptness in verbal communication among students signifies their proficiency in articulating Arabic with fluency and alacrity, devoid of significant hindrances in mutual comprehension. Secondly, instances of imprecisions in the enunciation of letters and linguistic norms emerge in specific scenarios. Thirdly, the direct transference from Gorontalo vernacular to Arabic manifests in sentences retaining the nuances of Gorontalo but articulated with Arabic lexicon. Fourthly, the impact of the mother tongue on the formulation of Arabic as the students' secondary language is discernible in the incorporation of particles within sentences. The outcomes of this research unveil that the attributes of the daily Arabic language usage by Pondok Pesantren Al-Falah's students are profoundly molded by the Gorontalo language. Despite the seamless communication among students, a requisite for refinement persists in their utilization of the Arabic language.